PROGRAM INTEGRASI LANSIA DAN REPRODUKSI (PILAR) DI BINA KELUARGA LANSIA DAN BINA KELUARGA REMAJA - DEWI, FETI KUMALA (P3M STIKES Aisyiyah Surakarta, 2018)
Health problem faced is health service of elderly and elderly with age 45 years old and above who get health service according to health standard either at community health centers or in integrated service post elderly group that is equal to 63,26%. This coverage still does not meet the target of 75%. Elderly Family Development and Youth Family Development is an active community organization implemented monthly, all within the reproductive age range, pre menopause and menopause. Participants are still in the reproductive and pre-elderly age range, so it still needs care and service family planning and healthy reproduction. Output target of this activity is the examination of blood sugar, cholesterol and uric acid as detection of Diabetes Militus disease, koleterol, gout and monitoring with control card of examination result. Improve Communication, Information and education about reproductive health and elderly health. The results of examination with necso tool in Elderly Family Development and Youth Family Development as a whole that is high blood pressure value 57 mother (36,31%), high blood sugar counted 8 mother (5,1%), high uric acid 52 mother (33,12%) and high cholesterol counted 14 mothers (8,92%). Knowledge before information about the highest reproduction health is less knowledge as much as 22 mothers (46,81%), after done the highest information is good knowledge as many as 21 mothers (44,68%). Knowledge before information about the highest health of elderly is knowledge of less than 49 mother (44,55%), after done the highest information is good knowledge as much 48 mother (43,64%).